2020
DOI: 10.3390/coatings10070700
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen-Based Hydrazones as Effective Corrosion Inhibitors for Mild Steel in 1.0 M HCl

Abstract: The corrosion-inhibiting performance of (E)-N’-(4-bromobenzylidene)-2-(6-methoxynaphthalen-2-yl) propanehydrazide (BPH) and (E)-N’-(4-(dimethylamino) benzylidene)-2-(6-methoxynaphthalen-2-yl) propanehydrazide (MPH) for mild steel (MS) in 1.0 M HCl was investigated using electrochemical methods, weight loss measurements, and scanning electron microscope (SEM) coupled with energy dispersive X-ray spectroscope (EDX) analysis. Raising the concentration of both inhibitors towards an optimal value of 5 × 10−3 M redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…They are widely used as catalytic, luminescent and energy materials, and for environmental purposes. [ 19–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used as catalytic, luminescent and energy materials, and for environmental purposes. [ 19–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…The more significant negative sign of ΔH in the presence of the inhibitors indicates an exothermic nature of the corrosion process, suggesting that the ionisation of steel surface is slow [ 27 ] in the presence of both MBC and HBM. A significant and positive value of entropy (ΔS) means that during the rate-determining step, the activated complex is formed via an association rather than a dissociation step [ 28 ], confirming that an increase in the disorder takes place when going from reactants to the activated complex.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed that the Langmuir adsorption model fitted well ( Figure 2 ) with a correlation coefficient (R 2 ) of 0.991 and 0.990 for MBC and HBM, respectively. The Langmuir equation is shown in Equation (5) [ 28 ]: where Ɵ is the surface coverage, C inh is the concentration of the MBC and HBM, and K ads is the equilibrium constant of the adsorption. The plot of the Langmuir adsorption model ( Figure 3 a) gives straight lines having high K ads values, indicating that both MBC and HBM molecules have strong interaction with the steel surface.…”
Section: Resultsmentioning
confidence: 99%
“…By extrapolation of the anodic and cathodic lines, the E cor and j cor values were obtained. The inhibition capacity (η pp /%) is calculated by Equation (1) as follows [39]:…”
Section: Pdp Studies and Comparative Evaluationmentioning
confidence: 99%